posted by .

differentiate and do not simplify:

Y=e^ -sq.rt x + e^3 - 2^(3x-1)

  • calculus -

    finally, a name

    Y=e^ -√x + e^3 - 2^(3x-1)
    Y=e^ -x^(1/2) + e^3 - 2^(3x-1)
    Y' = e^ -x^(1/2)(-1/2)x^(-1/2) + 0 - ln2(2^(3x+1))(3)

  • calculus -

    y = e^-(x^.5) + e^3 -2^(3x-1)

    .5x^(-.5) e^-(x^.5) + 0 - 3[2^(3x-1)]*ln2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. trigo help!

    1. differentiate cos(3/x) 2. differentiate sin(4/x) 3. differentiate 3/{sin(3x+pi)} 4. differentiate pxsin(q/x)where p and q are constants. 5. differentiate xsin(a/x) where a is constant 6. differentiate sec^3(3x^2+1)
  2. calculus

    Differentiate and simplify completely. [x^2(1-x)^3] / [(1+x)^3]
  3. calculus

    Differentiate and do not simplify: Y=x^2 * 3^2x
  4. calculus

    Differentiate and do not simplify: Y=e^-sq.rt.x + e^3 - 2^(3x-1)
  5. calculus

    Differentiate and do not simplify. y= e^(- sq.rt x) + e^3 - 2^(3x-1)
  6. calculus

    I have been asked to solve this two different ways. The first way is to use the chain rule and then simplify (which I have already done properly), and the second way is to simplify and then differentiate (not necessarily with the chain …
  7. Calculus

    Differentiate the following ( do not simplify) a) ln(√sinx)
  8. Calculus

    How do I differentiate ln (2X^2 - 12X + Y^2 -10Y) and the second differentiate it?
  9. Calculus

    I'm having problems with this one. Can't get the right answer. Differentiate the following using the chain rule. f(x) = squareroot(x^2+1)/(3x+1) I know that I can take the whole thing and put it to the (1/2) and differentiate that …
  10. Calculus-Math

    Complete the table without using the Quotient Rule. Function y=2x^(7/2)/x Rewrite y= Differentiate y'= Simplify y' =

More Similar Questions